Arabidopsis Auxin Mutants Are Compromised in Systemic Acquired Resistance and Exhibit Aberrant Accumulation of Various Indolic Compounds(1)([W])([OA]) - Truman, William M. (American Society of Plant Biologists, 2010)
Systemic acquired resistance is a widespread phenomenon in the plant kingdom that confers heightened and often enduring immunity to a range of diverse pathogens. Systemic immunity develops through activation of plant disease resistance protein signaling networks following local infection with an incompatible pathogen. The accumulation of the phytohormone salicylic acid in systemically responding tissues occurs within days after a local immunizing infection and is essential for systemic resistance. However, our knowledge of the signaling components underpinning signal perception and the establishment of systemic immunity are rudimentary. Previously, we showed that an early and transient increase in jasmonic acid in distal responding tissues was central to effective establishment of systemic immunity. Based upon predicted transcriptional networks induced in naive Arabidopsis (Arabidopsis thaliana) leaves following avirulent Pseudomonas syringae challenge, we show that a variety of auxin mutants compromise the establishment of systemic immunity. Linking together transcriptional and targeted metabolite studies, our data provide compelling evidence for a role of indole-derived compounds, but not auxin itself, in the establishment and maintenance of systemic immunity.